Analisis Faktor-Faktor yang Mempengaruhi Rendahnya Kemampuan Menulis Peserta Didik Kelas Redah di Sekolah Dasar - Fadhilah Nurlaily; Khavisa Pranata (Universitas Pendidikan Mandalika, 2022)
This study aims to analyze the factors that cause the low writing ability of Elementary School grade 1 students at Nurul Huda Islamic Elementary School after two years of students participating in online learning activities. The research used a qualitative approach with the type of case study research. First-graders, first-grade teachers, and the principal of SD Islam Nurul Huda were the subjects. In-depth interviews, documentation, field notes, and observation were the data gathering methods used in this study. The data analysis method applied was the Miles and Huberman analysis method, which entails three concurrent streams of activity: data reduction, data presentation, and conclusion drawing or verification. The result shows that student learning capacity has been negatively impacted by the Covid-19 epidemic, notably regarding their writing abilities. The causes are as follows: (1) the neglectful and uninvolved parental role at home, (2) family environmental factors, and (3) the student environment.